Analisis Krisis Energi Listrik di Kalimantan Barat - Arsyad, M. Iqbal (Faculty of Engineering, Universitas Tanjungpura, 2009)
Abstract Electrical sector plays important role in social-economy development of a country. Good electrical sector will accelerate the development of the other community development sectors. Therefore, the availability and sustainability of electrical sector must be maintained. Electrical energy crisis in Indonesia, including Kalimantan Barat, has its effects on the development of this region. This paper presents some aspects of electrical sector in Kalimantan Barat, both in supply side and demand side. Keywords Electrical sector, electrical energy crisis, supply side, demand side.